Early diagnosis, treatment, and outcomes of five patients with acute thallium poisoning - Wang, Ting-Ting (World J Clin Cases, 2021)
BACKGROUND: Thallium poisoning is rare and difficult to recognize. Early diagnosis and treatment of thallium-poisoned patients are essential to prevent morbidity and mortality. AIM: To evaluate the efficacy of treatments and outcomes of five patients with early diagnosis of acute thallium poisoning. METHODS: Five patients who consumed a thallium-contaminated meal were hospitalized in succession, and underwent clinical examinations such as blood tests and electromyography tests. Urine and blood tests confirmed the diagnosis of thallotoxicosis, revealing the occurrence of food poisoning. All patients underwent detoxification treatment, including hemoperfusion (HP) and treatment with Prussian blue (PB). A 24-mo follow-up was performed to evaluate the long-term outcomes on the patients after discharge. RESULTS: Initially, the patients presented with symptoms of acute thallium poisoning including hyperalgesia of the limbs and abdominalgia, which may differ from common peripheral neuropathy. Accompanying symptoms such as hepatic damage and alopecia were observed in all the patients, which further confirmed the diagnosis of poisoning. Treatment with chelating agents was ineffective, while HP and treatment with PB drastically decreased the thallium concentration in the urine and blood. With early diagnosis and intervention, four patients had a good prognosis and no permanent sequelae. One patient developed blindness and disability during the 24-mo follow-up period. CONCLUSION: Identification of incident cluster and characteristic symptoms is extremely important for early diagnosis of acute thallium poisoning. HP plus PB is essential to improve the prognosis of thallium-poisoned patients.